(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2024)
This article discusses about Inclusive Language Teaching and Strategies in educational settings. It explores the benefits of them and it’s effective sides for teaching. The author presents arguments supporting the process, overview real-world language use in curricula and highlights the impact of it for overall academic success. Additionally, the article acknowledges potential challenges and offers suggestions for overcoming them. Overall, it advocates for the significance of language instruction that refers to an approach in language teaching and learning that prioritizes the communication of meaning over the explicit focus on isolated language forms such as Inclusive Language Teaching instruction that refers to an approach in language teaching and learning that emphasizes the explicit focus on linguistic forms such as grammar, vocabulary, pronunciation, and syntax